2002
DOI: 10.1243/0954405021519960
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative development using EMProDS: The electromechanical product design system

Abstract: Among manufactured products, electromechanical devices are something of a special case, requiring input at the earliest design stage of experts from two (or more) distinctly separate branches of engineering. This tends to promote a modular approach under which products are partitioned by function, with each module being either purely electrical or purely mechanical. However, customers' demands for smaller lighter, less expensive items with greater functionality force manufacturers to produce integrated systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Constraint networks, agent-based systems, structural modeling and simulation tools and concurrent engineering approach have been developed to help the designer to improve complex product designs by avoiding conflicts and failures [1,2,3,4,5], but little progress has been made towards the use of these approaches for complex product design [6]. Various authors have shown that conflict management, information sharing, and integration become critical in advanced electromechanical design [6,7,8,9]. Despite a rapid growth and widespread use of mechanical and electronic CAD tools, there is still need for appropriate methods and tools for developing better and more durable complex systems.…”
Section: Introductionmentioning
confidence: 99%
“…Constraint networks, agent-based systems, structural modeling and simulation tools and concurrent engineering approach have been developed to help the designer to improve complex product designs by avoiding conflicts and failures [1,2,3,4,5], but little progress has been made towards the use of these approaches for complex product design [6]. Various authors have shown that conflict management, information sharing, and integration become critical in advanced electromechanical design [6,7,8,9]. Despite a rapid growth and widespread use of mechanical and electronic CAD tools, there is still need for appropriate methods and tools for developing better and more durable complex systems.…”
Section: Introductionmentioning
confidence: 99%